The French reception of Francis Bacon’s natural history in mid seventeenth century - Jalobeanu, Dana (ENS Éditions, 2014)
Francis Bacon’s natural historiesIn the last five years of his life, Bacon was actively engaged in a process of re-fashioning his natural philosophical project around a redesigned notion of natural history. Although always a core element in the Baconian programme, the notion of natural history had a fluctuating meaning: it meant simply a large repository of facts and data for the use of inductio, as well as a more theoretical topical construction of experiments, observations, questions, suggestions...